Insights From Dynamic Neuro-Immune Imaging on Murine Immune Responses to CNS Damage - Dorand, R. Dixon; Benson, Bryan L.; Huang, Lauren F.; Petrosiute, Agne; Huang, Alex Y. (Frontiers in Neuroscience, 2019)
Technological advances in 2-Photon Laser Scanning Microscopy (2P-LSM) have allowed novel insights into in vivo immune response in a variety of tissue microenvironments. While imaging of peripheral tissues has provided an abundance of data with regards to immune cell dynamics, central nervous system (CNS) imaging is comparatively inhibited by tissue accessibility and manipulation. Despite these limitations, the results of dynamic intravital neuro-immune imaging thus far have provided foundational insights into basic CNS biology. Utilizing a combination of intravital and ex vivo 2P-LSM we have observed novel pathways allowing immune cells, stromal cells, cancer cells and proteins to communicate between the CNS parenchyma and peripheral vasculature. Similar to what has been reported in the intestinal tract, we have visualized myeloid cells extend dendritic processes across the blood brain barrier (BBB) into pial blood vessels. Furthermore, transient vessel leaks seen during systemic inflammation provide opportunities for cellular protein to be exchanged between the periphery and CNS. These insights provide new, visual information regarding immune surveillance and antigen presentation within the CNS. Furthermore, when combining intravital 2P-LSM and microfluidic devices complexed with mathematical modeling, we are gaining new insights into the intravascular behavior of circulating immune cells. This new knowledge into the basic mechanisms by which cells migrate to and interact with the CNS provide important considerations for the design of neuroelectric devices that have the potential to connect the peripheral-neural microenvironments in a unique, artificial interface.